Boganmeldelser - Ina Eliasen; Lena Hellblom Sjögren; Kjersti Ericsson; Beth Grothe Nielsen; Kerstin Svensson; Ulla Høg; Sverker Jönsson; Paul Larsson; Peter Garde; Vagn Greve; Britta Kyvsgaard (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews